2019
DOI: 10.3346/jkms.2019.34.e29
|View full text |Cite
|
Sign up to set email alerts
|

Psychological Responses among Humidifier Disinfectant Disaster Victims and Their Families

Abstract: To substantiate psychological symptoms following humidifier disinfectant (HD) disasters, counseling records of 26 victims and 92 family members of victims (45 were bereaved) were analyzed retrospectively. Among the victims, 34.6% had Clinical Global Impression-Severity scores of over 4, which meant they were moderately ill. While anxiety/fear and depression with respiratory symptoms were frequently observed in victims and family members, chronic psychological distress such as alcohol/smoking abuse and insomnia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 15 publications
1
11
0
1
Order By: Relevance
“… 26 Currently, the injuries caused by HDs are expanding into the field of mental health and this contributes to the illogical nature of the existing victim classification system. 27 28 This demonstrates the need to expand the list of acknowledged HD-related injuries in a bid to assess individual's claims by conducting individual-based evaluation to listen to the victim's account and to comprehensively assess their diseases.…”
Section: Discussionmentioning
confidence: 99%
“… 26 Currently, the injuries caused by HDs are expanding into the field of mental health and this contributes to the illogical nature of the existing victim classification system. 27 28 This demonstrates the need to expand the list of acknowledged HD-related injuries in a bid to assess individual's claims by conducting individual-based evaluation to listen to the victim's account and to comprehensively assess their diseases.…”
Section: Discussionmentioning
confidence: 99%
“…The most common psychological symptoms in patients with HD-ILDs as well as their family members are anxiety, followed by fear and depression. 42) The bereaved of the patients with HD-ILDs showed higher rates of alcohol and smoking abuse and insomnia than those of other psychologic responses. 42) Therefore, support for psychologic health is urgently needed along with monitoring of the health of patients with HD-ILDs and their family.…”
Section: Psychologic Health In Patients With Hd-ildsmentioning
confidence: 98%
“…Also, a study that conducted a maladaptive cognitive emotion regulation survey of 40 victims of humidifier disinfectants in 2018 concluded that those with insomnia, depression, and PTSD were more likely to engage in self-blame, repetitive rumination on the past, and catastrophizing of the government's late response [6]. A survey of 26 victims at the National Mental Health Center in 2018 also revealed anxiety disorders (10 cases, 38.5%) and depression (10 cases, 38.5%) [4].…”
Section: Mental Health Impact On a Humidifier Disinfectant Victimmentioning
confidence: 99%
“…Despite the fact that not only physical injury has been linked to humidifier disinfectants, but also emotional and mental injuries-such as post-traumatic stress disorder (PTSD), depression, and suicide attempts due to the death of family members-the recognition criteria have not been reviewed [3,4]. Researchers and the government have focused on identifying causality of physical injury related to humidifier disinfectants; however, physical injury in these cases also leads to unintentional abusers and victims in the family.…”
mentioning
confidence: 99%